PERBANDINGAN PEMBAGIAN HARTA WARIS DALAMPERSPEKTIF HUKUM ISLAM DAN HUKUM ADAT - Iswawan Sulaiman; Ibnu Jazari; Khoirul Asfiyak (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2019)
Islamic inheritance law is a rule that regulates the transfer of property from a deceased person to another person to give property to an heir who is part of obtaining inheritance according to the portions that have already become a portion that will divide to the heirs given by the heir.